2016
DOI: 10.1155/2016/1424582
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Calibration of GE Healthcare Lunar Prodigy and iDXA Dual-Energy X-Ray Densitometers for Bone Mineral Measurements

Abstract: In long-term prospective studies, dual-energy X-ray absorptiometry (DXA) devices need to be inevitably changed. It is essential to assess whether systematic differences will exist between measurements with the new and old device. A group of female volunteers (21–72 years) underwent anteroposterior lumbar spine L2–L4 (n = 72), proximal femur (n = 72), and total body (n = 62) measurements with the Prodigy and the iDXA scanners at the same visit. The bone mineral density (BMD) measurements with these two scanners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Fourth, in the present study, only GE DXA was used, and the reference database should be used for GE DXA; however, the absolute BMD value varied in DXA manufacturers; therefore, the reference database generated in this study should not be used in other DXA machines. On other hand, the BMD value by different DXA manufacturers are highly correlated; if proper cross‐calibration procedure is taken, then the results from this study can be transferred to another DXA machine …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, in the present study, only GE DXA was used, and the reference database should be used for GE DXA; however, the absolute BMD value varied in DXA manufacturers; therefore, the reference database generated in this study should not be used in other DXA machines. On other hand, the BMD value by different DXA manufacturers are highly correlated; if proper cross‐calibration procedure is taken, then the results from this study can be transferred to another DXA machine …”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the calibration materials and equations used to derive lean mass should be standardized across manufacturers or cross‐manufacturer algorithms should be developed by industry to standardize the output. It is also important to standardize the local regions of interest, such as trunk, arms, and legs, which are significantly different across manufacturers …”
Section: Measurement Of Lean Body Mass and Muscle Mass With Imaging Tmentioning
confidence: 99%
“…The excellent BMD correlation between iDXA and Prodigy is well-demonstrated in previous studies, but the inconsistencies of BMD between 2 machines are an ongoing issue. [14][15][16]35] The smaller pixel size further enhances the bone edge detection of iDXA, which stands out for small bones such as the hands and feet. [38] However, edge detection might be attenuated as the automated analysis techniques might place edges or regions of interest more in large bones.…”
Section: Discussionmentioning
confidence: 99%
“…1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The studies identified for the meta-analysis involved 1,233 participants, with women comprising 808 (65.5%) of the sample population. Among the 14 studies, 8 articles compared PB and FB modes and other 6 studies compared FB and most recent FB mode (Table 1).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation